Pilot based channel estimation in amplify-and-forward MIMO relay networks - Jian ZHOU; Bao-yu ZHENG (Tongxin xuebao)
A channel estimation method in two time slots for two-hop amplify-and-forward MIMO relay channels is pro-posed.An algorithm for computing the optimal pair of source pilot and relay amplify matrix is developed,which mini-mizes the mean square error of the source-to-relay channel estimation subject to both power constraints at the source and the relay.The signal matrices are decomposed into unitary components and diagonal components.Then the bisection method is used to obtain the optimal diagonal components of the source pilot and the relay amplified matrix.The simula-tion results show that the proposed method has no ambiguity in the channel estimates.The effects of the channel correla-tion and the number of antennas on the performance of channel estimation are also analyed.